2006
DOI: 10.1186/1744-9081-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response characteristics of methylphenidate on locomotor behavior and on sensory evoked potentials recorded from the VTA, NAc, and PFC in freely behaving rats

Abstract: BackgroundMethylphenidate (MPD) is a psychostimulant commonly prescribed for attention deficit/hyperactivity disorder. The mode of action of the brain circuitry responsible for initiating the animals' behavior in response to psychostimulants is not well understood. There is some evidence that psychostimulants activate the ventral tegmental area (VTA), nucleus accumbens (NAc), and prefrontal cortex (PFC).MethodsThe present study was designed to investigate the acute dose-response of MPD (0.6, 2.5, and 10.0 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…The above reports indicate that LC neurons are electrophysiological quiet during low vigilance states such as sleep or in the lack of sensory input, while during active walking or exposed to a strong stimulus, the LC neurons markedly increase its firing rate. Consistent with the above studies, the present experiment found that after administration of MPD most of LC units significant increase their firing rate, since administration of MPD (2.5mg/kg or above) resulted in an increase in locomotor activity (Askenasy et al, 2007;Gaytan et al, 2000a; 2000b; 2002;Yang et al, 2003a; 2006a; 2006b; 2006c; 2007; 2010). …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The above reports indicate that LC neurons are electrophysiological quiet during low vigilance states such as sleep or in the lack of sensory input, while during active walking or exposed to a strong stimulus, the LC neurons markedly increase its firing rate. Consistent with the above studies, the present experiment found that after administration of MPD most of LC units significant increase their firing rate, since administration of MPD (2.5mg/kg or above) resulted in an increase in locomotor activity (Askenasy et al, 2007;Gaytan et al, 2000a; 2000b; 2002;Yang et al, 2003a; 2006a; 2006b; 2006c; 2007; 2010). …”
Section: Discussionsupporting
confidence: 91%
“…Previous dose response experiments using MPD from 0.1 to 40 mg/kg found that 2.5 mg/kg MPD (i.p.) elicited behavioral and neurophysiological sensitization ( Gaytan et al, 1996;Lee et al, 2009; Podet et al, 2010;Yang et al, 2001; 2003b; 2006a; 2006c; 2007; 2010; 2011). Thus, the 2.5 mg/kg MPD dose was used in this experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acute dose response for the 2.5 and 10.0 mg/kg MPD groups (moderate and high MPD doses [8]) shows increases in locomotor activity in comparison to their baseline recordings (Figure 2). This is expected: prior MPD dose response experiments have shown similar results [16]- [21] [25] [37], indicating that chronic MPD administration elicits persistent changes in the CNS [38] [39].…”
Section: Response Characteristics Of Ethanol Alone and After Chronic mentioning
confidence: 60%
“…), are calculated as freebase. Dosages were selected from prior MPD dose response studies [6] [14]- [19] [21]. These studies assessed the dose responses of eight different concentrations of MPD, in which three were selected.…”
Section: Drugsmentioning
confidence: 99%